Istikhdām Wasīlah al-Kalimāt al-Mutaqāṭi‘ah fī Tanmiyat Mahārah al-Kitābah li-Ṭālibāt al-Faṣl al-Sābi‘ fī al-Madrasah al-Mutawassiṭah “al-Khadījah” Jombang - Masita, Iza; Isniyatun Niswah, Isniyatun (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
Writing skill is a language skill that expresses or describes the content of thoughts from  simple things to complex things. The focus of this research are (1) Student al-chodijah Jombang Junior High School are able to write and arrange random words, (2) Student  al-chodijah Jombang Junior High School are able to complete sentence from mufrodat, (3) Student al-chodijah Jombang Junior High School are able to translate Arabic sentence into Indonesian. This study used descriptive qualitative method, This study descriptive the use of crossword puzzle in increasing the writing skill for learning Arabic, how the advantage and disadvantage of using crosswords media in increasing the writing skill student of class seven grade al-chodijah Junior High School Jombang. Arabic learning activities and supporting factors for Arabic language development. Data obtained through observation, interview, and documentation. Data analysis using data reduction, data presentation and data inference. The result of the research obtained are yhis is evidenced by the percentage of writing skills at the meeting, memely in the pre-study, in the first cycle 16,67% and in the second cycle 41,6%. The increase in the percentage of student from cycle one to cycle two in the educational process was 58.3% . it can be concluded that there is an increase in teaching writing skills using crosswsord puzzles among the sevent grade student of SMP al-Chodijah Jombang Junior High School.